2017
DOI: 10.1007/s00345-017-2108-3
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced recovery after surgery for radical cystectomy with ileal urinary diversion: a multi-institutional, randomized, controlled trial from the Chinese bladder cancer consortium

Abstract: ERAS did not increase 30-day complications compared with CRAS after RC. ERAS may be better than CRAS in terms of bowel movement, tolerance of fluid and regular diet, and ambulation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
49
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 51 publications
(51 citation statements)
references
References 25 publications
2
49
0
Order By: Relevance
“…In our meta-analysis, a shorter time to defecation in comparison to traditional regimes in pooling of all patients could be shown. Still, in the RCT-group only Frees et al [3] could show a significantly shorter time to defecation, whereas the RCT with the larger cohort by Lin et al [7] as well as pooling of the two RCTs showed no significant difference.…”
Section: Discussionmentioning
confidence: 85%
See 1 more Smart Citation
“…In our meta-analysis, a shorter time to defecation in comparison to traditional regimes in pooling of all patients could be shown. Still, in the RCT-group only Frees et al [3] could show a significantly shorter time to defecation, whereas the RCT with the larger cohort by Lin et al [7] as well as pooling of the two RCTs showed no significant difference.…”
Section: Discussionmentioning
confidence: 85%
“…Prospective studies on ERAS implementation could show that length of stay (LOS) can be reduced [5][6][7] although few studies found no significant difference [8]. Regarding complications after RC, the majority of prospective studies showed no significant difference for implementation of an EP [5,9] whereas few studies could show a lower complication rate [10].…”
Section: Introductionmentioning
confidence: 99%
“…Two more studies with identical data sets were also excluded. Finally, seven RCTs ( 6 12 ) evaluating the recovery effect of radical cystectomy between ERAS protocols and CRAS protocols were included in the analysis ( Figure 1 ). The baseline characteristics of the studies are presented in Table 2 .…”
Section: Resultsmentioning
confidence: 99%
“…In all the RCTs included in our study, age, sex, and operation type of the patients were the indicator types analyzed. Concerning operation type, 538 patients from the seven RCTs (6)(7)(8)(9)(10)(11)(12) underwent open radical cystectomy. Three RCTs (8, 9, and 12) included 81 patients who underwent robot-assisted radical cystectomy.…”
Section: Discussionmentioning
confidence: 99%
“…In patients undergoing colorectal, urologic, gastric and pancreatic surgery substantial patient and healthcare benefits were acquired with the implementation of ERAS protocols by decreasing LOS, complication rate, and lowering hospital costs [19][20][21][22]. ERAS principles have also long been used in women undergoing major gynecologic surgery.…”
Section: Discussionmentioning
confidence: 99%